UPAYA MENINGKATKAN PROSES DAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN METODE PICTURE AND PICTURE DALAM PEMBELAJARAN IPA KELAS III SDN 105/II DESA RAMBAH - SUBHANADRI SUBHANADRI; Ririn Indriyani (Jurnal Tunas Pendidikan, 2018)
This research is motivated by groupings that only use the lecture method without using media in the application of students who are not active in learning such as group discussions and asking questions. In addition, from the data obtained by students' science learning outcomes are still low, which is still below the Minimum Completion Criteria (KKM), which is 70. This study aims to improve Student Learning Processes and Results by using Image and Image Methods in Science Learning. The design of this study is classroom action research using two cycles, each cycle consisting of four stages, namely planning, implementation, and reflection. The research subjects were teachers and third grade students of Public Elementary School No.105 / II in Rambah Village who practiced 36 students. Data collection techniques use teacher performance measurements and tests. The results showed that the teacher in the first cycle of my meeting got a score of 69.32% with good criteria, meeting II with a score of 72.73% with good criteria. In the second cycle my meeting with a score of 82.95% criteria was very good, in the second cycle of the second meeting with a score of 100%. And classical completeness of student learning outcomes in the first cycle of meeting I was 33% and the first cycle of meeting II was 50%. In the second period, the first meeting was 67% and the second meeting was 94%..